(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
School resources comprise of necessary materials both financial and human. A growth towards evidence-based allocation and utilization of school resources is affected by inadequate capacity of the school managers, ministry of education, parents and non-governmental organizations. Inadequate teaching and learning resources limits individual schools’ strength to make judicial decisions on equitable trade-offs in education resource demand, supply and consumption. This paper sought to identify the locally available resources for utility in competency-based- curriculum implementation; ways of improving the available resources for enhancing teaching and learning; and analyze factors militating against effective mobilization and utilization of resources at basic education level. Online surveys were used in collecting secondary data. Stratified sampling technique was used in obtaining data from journals, internet, textbooks and research reports. The findings showed that the rural urban migration factors significantly affect trained teachers from arid and semi- arid areas by moving away from their local homes to towns in search for jobs. When learners fail to interact adequately with trained teachers, the consequences are dire resulting to poor acquisition of competencies by learners. The paper established that more than 70% of the teachers teaching at Kakuma Refugee Camp were not sensitive to learner’s plights. Furthermore, 60% of the tutors at Kakuma Refugee Camp are untrained in pedagogical and andragogical skills necessary for giving instructions in competency-based-curriculum. The critical mass of activities under CBC including disciplines such as arts, music, and sports all creates new opportunities of supply chains that present avenues for partnering with organizations that support basic education activities. The paper established that the cost of needed materials and trainings for improving implement the CBC was expensive and therefore; action research could explore avenues for economies of scale by sharing materials, orders and coordinating purchases between and among neighbourhood schools. In conclusion, the national and County government’s department of preprimary and basic education should generate guidance on the use of alternative and low-cost materials for teaching so as to alleviate the persistence shortages of teaching resources.